Viewpoints and behaviour patterns of professionally active nurses concerning work–life balance - Sobczak, Marzena; Budzińska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The problem of the lack of harmony between a career and personal life and its consequences have been recently analyzed among people who are professionally active. In order to meet the requirements that are imposed by employers, employees often have to sacrifice their personal life for fulfilling career aims. They accept working conditions specified by employers despite the fact that they often lead to upsetting work-life balance. The issues that are presented in the article refer to work-life balance. A group of professionally active nurses from the town and the commune of Biskupiec constitute the representative group. Aim. The aim of the article was to evaluate opinions and behaviour patterns of professionally active nurses in reference to their careers and private lives. Material and methods. The research material constituted 101 nurses working in the town and commune of Biskupiec. The group varied in family life, forms of employment, working places and working experience. The diagnostic poll method was used. The research tools comprised the survey compiled by the authors, work-life balance scale (based on the theory by Smith and Gardner) and the work–home balance scale put forward by Karasiewicz, Godlewska-Werner, Lewandowska-Walter and Piotrowski. Results. There are differences between opinions and behaviour patterns in reference to work-life balance. The fact that they have their own passions and some of the socio-demographic variables influence how nurses function in their private and professional lives. Conclusions. The respondents have problems with separating their professional lives from private ones. Behaviour patterns concerning work–home and home–work balance do not correspond to their viewpoints. There is a need to raise nurses’ awareness of the importance of maintaining work–home and home–work balance. Nursing Topics 2014; 22 (2): 184–189